Holistic approach to assess the association between the synergistic effect of physical activity, exposure to greenspace, and fruits and vegetable intake on health and wellbeing: Cross-sectional analysis of UK Biobank - Cruz-Piedrahita, Catalina; Roscoe, Charlotte J.; Howe, Caroline; Fecht, Daniela; de Nazelle, Audrey (Frontiers in Public Health, 2022)
Background: Urban agriculture projects have been shown to contribute to healthy lifestyle behaviours such as increased fruits and vegetable intake and exposure to greenspaces. There is plenty of evidence linking these lifestyle behaviours to better health and well-being, however, most of the evidence has only assessed one behaviour at a time and there has been limited epidemiological research on evaluating the combined effects of multiple behaviours on health and well-being. Methods: We used data from the UK Biobank's baseline questionnaire to assess the association between three lifestyle behaviours (fruits and vegetable intake, physical activity, and greenspace exposure) with six health and well-being markers (Systolic and diastolic blood pressure, waist to hip ratio, self-health assessment, self-reported loneliness, and medication intake for tension, anxiety, depression, or nerves) independently and combined. Lifestyle behaviours and interactions were explored using ordinal and gaussian generalised additive models (GAMs) and adjusted for confounders (age, gender, qualifications, Index of multiple deprivation, ethnicity, alcohol, and smoking status) Results: The models indicate that lifestyle behaviours have independent impacts on health and well-being, but that interactions between them indicate synergistic benefits, above and beyond that of the sum of the independent effects. The results show that the association between lifestyle behaviours, including any synergistic effects and health and well-being markers are not always positive, and not specifically dose related. However, on average, values close to the WHO recommended levels of fruits and vegetable intake and physical activity are linked to better health and well-being markers in general. Conclusion: Healthy diets, physical activity and exposure to greenspace have synergistic benefits on health above and beyond that of the additive effects of these behaviours observed independently. Promoting such behaviours together, such as through urban agriculture, is thus likely to generate greater public health benefits than when they are promoted through independent policies and programs. Inter-relationships between these pathways and different health impacts, however, are complex, and require further investigation to understand optimal environments and conditions for urban health promotion.\